Elaboración y conservación con fines agroindustriales y comerciales de la chicha de jora y quinua en las comunidades beneficiarias del proyecto "runa kawsay" - Parévalo Chaverrea, María Paulina (2011)
This research project had the support and participation of project beneficiaries "RUNA KAWSAY", since in these communities as in other provinces. The problems of food are marked by a lack of healthy feed that has affected in the health status of the indigenous population has had the need to restore what once was considered the drink of the gods, chicha source of many nutritional values.